2005
DOI: 10.1093/treephys/25.9.1109
|View full text |Cite
|
Sign up to set email alerts
|

Drought effects on hydraulic conductivity and xylem vulnerability to embolism in diverse species and provenances of Mediterranean cedars

Abstract: We studied hydraulic traits of young plants of the Mediterranean cedar species Cedrus atlantica (Endl.) G. Manetti ex Carrière (Luberon, France), C. brevifolia (Hook. f.) Henry (Cyprus), C. libani A. Rich (Hadeth El Jebbe, Lebanon) and C. libani (Armut Alani, Turkey). With an optimum water supply, no major differences were observed among species or provenances in either stem hydraulic conductivity (Ks) or leaf specific conductivity (Kl) measured on the main shoot. A moderate soil drought applied for 10 weeks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 47 publications
6
49
0
5
Order By: Relevance
“…Positive values correspond to a safety margin, negative ones reveal a lack of control of stomata over cavitation. Data from [109]; [47]; [81]; Huc et al, unpublished; [92]; [31]; [28]; [3]; Cochard et Ameglio, unpublished. margin [135]. In most tree species, this margin is narrow, meaning that tree transpiration operates close to the cavitation induction point (Fig.…”
Section: Vulnerability To Cavitation and Stomatal Conductance: Couplimentioning
confidence: 99%
See 2 more Smart Citations
“…Positive values correspond to a safety margin, negative ones reveal a lack of control of stomata over cavitation. Data from [109]; [47]; [81]; Huc et al, unpublished; [92]; [31]; [28]; [3]; Cochard et Ameglio, unpublished. margin [135]. In most tree species, this margin is narrow, meaning that tree transpiration operates close to the cavitation induction point (Fig.…”
Section: Vulnerability To Cavitation and Stomatal Conductance: Couplimentioning
confidence: 99%
“…Within an organ, wider conduits are generally more susceptible to drought-induced cavitation, but across organs or species this trend is very weak [64,81]. This is probably because the cavitation threshold is generally not determined by vessel diameter but by the pore diameter in conduit walls [156].…”
Section: Vulnerability To Drought-induced Cavitationmentioning
confidence: 99%
See 1 more Smart Citation
“…brevifolia is well-differentiated from other species of the genus based on morphological and ecophysiological traits such as short needles and slow growth, resistance to aphids, and the highest tolerance to drought in all cedar species (e.g. Vidakovic 1991;Ladjal et al 2005). In contrast, phylogenetic studies on cedar species have shown a strong genetic relationship between C. brevifolia and its widespread congener C. libani, especially with populations from Turkey (Scaltsoyiannes 1999;Fady et al 2000;Bou Dagher-Kharrat et al 2007;Qiao et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Roots are the primary organ for the absorption of water and minerals, and drought greatly affects the number and size of water conducting elements, a functional aspect related to root anatomy [12]. Reduction in cortical cell size and number, lignification of epidermal and exodermal cells and layering of sclerenchymatous cells in neighbour of cortical cells are due to the deposition of lignin, and suberins is one of another modifications under water deficit condition [13].…”
Section: David Publishingmentioning
confidence: 99%